2018
DOI: 10.1111/jopy.12374
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional malevolence and impression formation: Dark Tetrad associations with accuracy and positivity in first impressions

Abstract: Interpersonal perceptions that included an individual scoring highly on one of the Dark Tetrad traits differed in important ways from interactions among individuals with more benevolent personalities. Notably, despite the similarities between the Dark Tetrad, traits had unique associations with interpersonal perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 80 publications
(143 reference statements)
3
25
1
Order By: Relevance
“…Previous research has demonstrated that certain dimensions of malevolent dispositions were linked to the perception of others as threat (Brankley & Rule, 2014), as well as the accuracy and positivity of the first impressions of others (Rogers et al, 2018). In our study, the females with more pronounced all four dark traits were less accurate in recognizing non-criminals and more accurate in recognizing criminals compared to those with less pronounced dark traits.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Previous research has demonstrated that certain dimensions of malevolent dispositions were linked to the perception of others as threat (Brankley & Rule, 2014), as well as the accuracy and positivity of the first impressions of others (Rogers et al, 2018). In our study, the females with more pronounced all four dark traits were less accurate in recognizing non-criminals and more accurate in recognizing criminals compared to those with less pronounced dark traits.…”
Section: Discussionsupporting
confidence: 43%
“…Specifically, the individuals high on dark traits usually have a negative view of others (e.g. Rogers, Le, Buckels, Kim, & Biesanz, 2018) and project their own unfavourable traits onto others (Black, Woodworth, & Porter, 2014;Mahaffey & Marcus, 2006;Rauthmann, 2012). Possible explanations for this negative view of others include their enhanced sensitivity to anger/hostility or the fact that they hold a negative other bias, i.e.…”
Section: Personality Traits and Appearance-based Implicit Judgementsmentioning
confidence: 99%
“…Finally, before taking into account knowledge about COVID-19, everyday sadism was a significant predictor of the tendency to believe in COVID-19 conspiracy theories. If misanthropy underlies the acts of cruelty committed by sadists, it is plausible that sadists would believe in conspiracy theories for the very same reason that Machiavellians do: They expect malfeasance from others (Međedović & Bulut, 2018;Rogers et al, 2018). However,…”
Section: Discussionmentioning
confidence: 99%
“…It is, nevertheless, plausible that one reason those high in everyday sadism derive pleasure from perpetrating acts of cruelty is because they think that other people deserve it. Sadism is, in fact, associated with cynicism (Međedović & Bulut, 2018), and sadistic individuals also tend to perceive others as being aggressive, demanding, and opportunistic (Rogers, Le, Buckels, Kim, & Biesanz, 2018). Those scoring high in sadism may believe in conspiracy theories because they think others would act nefariously if given the chance.…”
Section: Sadism and Conspiracist Ideationmentioning
confidence: 99%
“…To this end, our lab is refining a Short Dark Tetrad questionnaire (SD4; Jones, Buckels, & Paulhus, ), which may help resolve measurement issues in the dark personality space. Even with imperfect assessment tools, meaningful differences emerge with methodology as varied as behavioral (Buckels et al, ; Carre & Jones, ; Jones & Paulhus, ; Pfattheicher et al, ; Rogers, Le, Buckels, Kim, & Biesanz, ), physiological (Dane, Jonason, & McCaffrey, ; Dufner, & Paulhus, ), and self‐report (Birkás, Gács, & Csathó, ; Burris & Leitch, ; Chabrol, Melioli, Van Leeuwen, Rodgers, & Goutaudier, ; Duspara & Greitemeyer, ; Jonason et al, ; Neria, Vizcaino, & Jones, ; Plouffe et al, ; Sagioglou & Greitemeyer, ).…”
Section: Limitations and Recommendations For New Directionsmentioning
confidence: 99%